2021
DOI: 10.21660/2021.79.gx168
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic Conductivity Characteristics of a Fine-Grained Soil Potential for Landfill Liner Application

Abstract: Sanitary landfills (SLFs) are usually employed as final waste disposal facility to protect public health and the environment. As a result of rapid population growth and urbanization, there is currently a great demand to construct SLFs in the Philippines. The hydraulic conductivity characteristics of remolded samples of a locally abundant fine-grained soil compacted at different compaction energy level is investigated to determine the suitability of the soil as landfill liner material. The hydraulic conductivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Thus, five trials were conducted to approximate the compaction moisture content that would yield an acceptable hydraulic conductivity of the compacted local clay. In which, the trial specimen for this study was targeted to have a similar hydraulic conductivity with the specimen from the study of Tiongson and Adajar [7,8] that used the same type of expansive soil from the same site in Kauswagan, Lanao del Norte. The compaction moisture content established from the trial tests was 46.5%, which was used in the mix proportion of the specimens used in the experimentation to obtain the hydraulic conductivity of the compacted polyurethane-clay.…”
Section: Proportionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, five trials were conducted to approximate the compaction moisture content that would yield an acceptable hydraulic conductivity of the compacted local clay. In which, the trial specimen for this study was targeted to have a similar hydraulic conductivity with the specimen from the study of Tiongson and Adajar [7,8] that used the same type of expansive soil from the same site in Kauswagan, Lanao del Norte. The compaction moisture content established from the trial tests was 46.5%, which was used in the mix proportion of the specimens used in the experimentation to obtain the hydraulic conductivity of the compacted polyurethane-clay.…”
Section: Proportionmentioning
confidence: 99%
“…The summary of the initial void ratio and the description of the manual compactive effort applied for the three kinds of compacted specimen are tabulated in Table 5. The compactive effort that produced the CCL, with an initial void ratio of 1.06, compaction moisture content of 46.5%, and an acceptable hydraulic conductivity based on the study of Tiongson and Adajar [7,8] that used the same type of soil, was applied to polyurethane-clay that produced the CPCL. CPCL had the same compactive effort as CCL, but a higher initial void ratio of 1.44.…”
Section: Manual Compactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mendoza et al [8] revealed that smectite in Manila indicates moderate to high plasticity indices and low hydraulic conductivity values ideal for landfill lining. Research by Tiongson and Adajar [9] on compacted clay linings was conducted in response to the imminent operation of a sanitary landfill in Kauswagan, Lanao del Norte, and nearby municipalities. Local soil samples intended as landfill lining material were identified as expansive soils.…”
Section: Introductionmentioning
confidence: 99%